The Influence of the COVID-19 Outbreak on the Lifestyle of Older Patients With Dementia or Mild Cognitive Impairment Who Live Alone - Hashimoto, Mamoru; Suzuki, Maki; Hotta, Maki; Nagase, Aki; Yamamoto, Yuki; Hirakawa, Natsuho; Nagata, Yuma; Satake, Yuto; Suehiro, Takashi; Kanemoto, Hideki; Yoshiyama, Kenji; Mori, Etsuro; et al. (Frontiers in Psychiatry, 2020)
Background: Under the coronavirus 2019 (COVID-19) outbreak, Japanese government has strongly encouraged individuals to stay at home. The aim of the current study was to clarify the effects of the COVID-19 outbreak on the lifestyle of older adults with dementia or mild cognitive impairment (MCI) who live alone. Methods: Seventy-four patients with dementia or MCI over 65 years old were recruited from patients who regularly visited the dementia clinic of the department of psychiatry, Osaka University Hospital. Patients were divided into two groups according to their living situation: a living alone group (n = 12) and a living together group (n = 62). Additionally, the spouses of the patients over 65 were examined as a healthy control group (n = 37). Subjects’ lifestyle changes were evaluated between 8 and 28 April 2020. Results: There were no subjects with acquaintances or relatives infected with COVID-19 within the study period. The proportions of subjects who reduced going out in the living alone group, the living together group and the healthy control group were 18.2%, 52.5%, and 78.4%, respectively. The proportion of subjects who went out less was significantly lower in both the living alone (p < 0.01) and living together groups (p < 0.05) compared with the healthy control group. Conclusion: Most patients with dementia or MCI who lived alone did not limit their outings or activities during the COVID-19 outbreak. Regular monitoring of potential COVID-19 infection in people living alone with dementia is critical for their safety and well-being.